Actualizing societal membership in imaginary interaction: The “real construction of society” in the opening of current affairs TV discussion - Rautajoki, Hanna (Frontiers in Sociology, 2023)
The wonder of modern mass-scale society has preoccupied sociological theorists for centuries. How does the whole live on and function? At the extreme of strong empirical traditions, conversation analysis focuses on studying the interactional organization of ongoing action and identities. My article puts these two inquiries together to explore the broader relevancies of situated talk and evidence the skillfulness of social actors in managing multi-scaled cultural memberships simultaneously. Approaching society as a processual accomplishment, this article investigates the instantiation of “societal membership” in a mundane institutional setting of broadcast television. The aim of the article is to experiment with how classical theoretical conceptualization can feed into methodological insight and how detailed empirical scrutiny can enrich our theoretical understanding of the mysteries of modern co-existence. This entails casting an analytic eye on the duality of structure and action. The article re-examines the structural scope of on-site interactional achievements. From an opposite angle, it highlights how integrative societal structures are made real and maintained in the art of interactional encounters. This two-way dynamic is exemplified by scrutinizing a fragment of a televised current affairs program. A set of theoretical key concepts is introduced to shed light on the societal orientations of participants in the opening talk of the program. The opening talk addresses an imaginary audience directly via the camera. It provides a view of the interactional methods used by journalists to invoke relevant identifications for the anticipated recipient at a distance. The encounter is imagined, yet instead of imagining a community in the reception, the analytic focus of the article is on actualizing society in the production of the talk. The spatially and temporally organized societal membership materializes in social relations and interdependencies, which are constituted through intersubjective interpretations, normative positionings, and interactional choices by intentional and knowledgeable actors in the routines of everyday life. The article reverse-engineers the relational framework of the deliberative public sphere enacted in mediated interaction as a collaborative scene of the democratic system. This is achieved by explicating the contextually embedded acts of societization taking place in a journalistically regulated field of participation by means of quasi-interactive public speech.